Namibia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper reports economic developments in Namibia during the 1990s. Since the early 1990s, average GDP growth has been higher than in the previous decade, owing to the opening of two new diamond mines, the extension of the limits of Namibia's coastal waters, and the rapid growth in government services. Real GDP grew by more than 5 percent in 1991-92, contracted by 2 percent in 1993, and expanded by 7 percent in 1994 and 5 percent in 1995. The allocation of domestic expenditure fluctuated during 1990-95.